Coping strategies and their associated factors among caregivers of patients with schizophrenia in Kuantan, Malaysia - Kamarulbahri, Tengku Mohd Saifuddin Tengku; Ariaratnam, Suthahar; Nikmat, Azlina Wati; Abdullah, Nik Nairan; Khing, Tan Lee (Frontiers in Psychiatry, 2022)
Background It is essential for caregivers of schizophrenia patients to have effective coping mechanisms to deal with their own mental health. However, research on the factors that contribute to the coping mechanisms of caregivers is limited. The purpose of this study is to investigate the use of coping strategies and their correlations to socio-demographic features, psychological distress, and social support among the caregivers of patients with schizophrenia. Method Through the convenience sampling method, 331 caregivers of patients with schizophrenia participated in this cross-sectional study. The respondents comprised caregivers who had attended an outpatient psychiatric clinic, providing the socio-demographic data. The study involves three instruments: the Kessler's Psychological Distress (K10); the Multidimensional Scale of Perceived Social Support (MSPSS); and the Brief-COPE. Findings Using multivariable analysis, psychological distress was identified as a substantial independent predictor of emotion-focused, problem-focused, and avoidance coping strategies. Good social support was linked to the usage of problem-focused and emotion-focused coping strategies. Conclusion It has been demonstrated that good social support and psychological distress are associated with coping strategies. More prospective and qualitative research is required to determine how coping strategies will be able to assist Malaysian caregivers to develop a more holistic approach to treating patients with schizophrenia.